Porous framework n-doped MXene-C-Au composite material and preparation method thereof

CN122907515APending Publication Date: 2026-10-13SHAANXI ANCHU TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611157138.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,现有贵金属掺杂方法存在以下缺陷:一是结构破坏风险,高温热处理易导致MXene失水氧化或层间结构坍塌;二是工艺复杂度高,通常需液相沉积、高温退火等多步操作,部分方法依赖昂贵设备并多次换溶剂清洗,不利于规模化生产;三是Au流失严重,真空干燥或热处理过程中未牢固结合的贵金属离子易逸出,导致负载率低、资源浪费

Benefits of technology

[0014]与现有技术相比,本发明的有益效果有:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907515A_ABST
    Figure CN122907515A_ABST
Patent Text Reader

Abstract

The application discloses a kind of porous framework N doped MXene-C-Au composite material and preparation method thereof.The method comprises: obtaining polymer porous foam;Then in inert atmosphere, with 2~5 ℃ / min heating rate, heat to 300~600 ℃ and keep for 2~4 h, obtain carbonized polymer porous foam;Carbonized polymer porous foam is immersed in MXene dispersion liquid and treated, and after drying, carbonized polymer porous foam containing MXene is obtained;Again, immerse in gold source precursor solution and stand for 0.5~1.5 min, and after drying, porous framework N doped MXene-C-Au composite material is obtained.The application makes MXene nanosheet and gold nanoparticle formed after reduction be uniformly distributed in the inner wall of porous foam structure by carbonized polymer porous foam, effectively improves the structural stability of composite material and metal loading rate, and is suitable for electrocatalysis, supercapacitor and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy storage materials technology, specifically relating to a porous framework N-doped MXene-C-Au composite material and its preparation method. Background Technology

[0002] Currently, two-dimensional transition metal carbonitrides (MXenes) have become ideal substrates for high-performance energy storage materials due to their metal-like high conductivity and abundant surface functional groups. Incorporating them into carbon substrates can effectively suppress interlayer stacking, retain a large specific surface area, and enhance electrocatalytic activity and conductive network, and they have been widely used in the research and development of electrocatalysis and supercapacitor electrodes.

[0003] To further enhance electrocatalytic activity and conductive networks, the introduction of trace amounts of noble metals (such as Au, Ag, Pd, and Pt) has become a consensus. Noble metals not only provide additional electron transport channels but also significantly enhance interfacial reaction kinetics. However, existing noble metal doping methods have the following drawbacks: First, there is a risk of structural damage, as high-temperature heat treatment can easily lead to MXene dehydration and oxidation or interlayer structure collapse; second, the process is highly complex, typically requiring multiple steps such as liquid-phase deposition and high-temperature annealing, with some methods relying on expensive equipment and multiple solvent changes for cleaning, which is not conducive to large-scale production; third, Au loss is severe, as poorly bound noble metal ions can easily escape during vacuum drying or heat treatment, resulting in low loading rates and resource waste.

[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, this invention provides a porous framework N-doped MXene-C-Au composite material and its preparation method. The technical problem to be solved by this invention is achieved through the following technical solution: In a first aspect, the present invention provides a method for preparing a porous framework N-doped MXene-C-Au composite material, comprising the following steps: S1. Obtain polymer porous foam; S2. The polymer porous foam is annealed in an inert atmosphere at a heating rate of 2-5℃ / min to 300-600℃ and held for 2-4 hours to obtain carbonized polymer porous foam. S3. The carbonized polymer porous foam is immersed in MXene dispersion for treatment, and after the first drying, carbonized polymer porous foam containing MXene is obtained; the concentration of MXene in the MXene dispersion is 5-20 mg / mL; S4. Immerse the MXene-containing carbonized polymer porous foam in the gold source precursor solution and let it stand for 0.5 to 1.5 min. After a second drying, a porous framework N-doped MXene-C-Au composite material is obtained.

[0006] In one embodiment of the present invention, step S1, obtaining polymer porous foam includes pretreatment of polymer porous foam raw materials; The pretreatment includes: cutting the polymer porous foam raw material to obtain a volume of 6-10 cm³. 3 Polymer porous foam blocks; The polymer porous foam block was ultrasonically cleaned in ethanol and then dried to obtain the polymer porous foam.

[0007] In one embodiment of the present invention, the polymer porous foam is one of melamine porous foam, phenolic resin porous foam and polyurethane porous foam.

[0008] In one embodiment of the present invention, in step S3, the MXene is a single-layer or few-layer MXene nanosheet; The MXene nanosheets were obtained by etching and exfoliation of the parent MAX material, and the chemical formula of the MXene nanosheets is M. n+1 X n T x Where n is a positive integer from 1 to 3, M is selected from any one of Sc, Ti, Zr, V, Nb, Cr and Mo, A is selected from any one of Al, Si and Ga, X is C and / or N, and T x It is a surface functional group.

[0009] In one embodiment of the present invention, the preparation process of the monolayer or few-layer MXene nanosheets includes: S31. At 30-40°C, the parent phase MAX material is subjected to liquid-phase etching reaction using an etching solution for 20-60 h to obtain two-dimensional nanosheets; wherein, the etching solution is a mixture of hydrogen fluoride and hydrochloric acid, or the etching solution is a mixture of lithium fluoride and hydrochloric acid. S32. The two-dimensional nanosheets are washed with deionized water until the pH of the washing solution is ≥6. After washing, the supernatant is collected by ice bath sonication and centrifugation to obtain a monolayer or few-layer MXene dispersion.

[0010] In one embodiment of the present invention, in step S3, the impregnation treatment time is 0.5 to 2 hours; The first drying process is carried out in a vacuum oven at a temperature of 50–100°C for 1–3 hours.

[0011] In one embodiment of the present invention, in step S4, the gold source precursor solution is an aqueous solution of HAuCl4, and the concentration of the aqueous solution of HAuCl4 is 3-7 mmol / L.

[0012] In one embodiment of the present invention, the second drying is performed using a vacuum oven, the second drying temperature is 50–100°C, and the second drying time is 10–15 h.

[0013] Secondly, the present invention provides a porous framework N-doped MXene-C-Au composite material, which is obtained by the above preparation method.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The preparation method provided by this invention utilizes the micropores of carbonized polymer porous foam as a scaffold to effectively capture and immobilize MXene nanosheets. Simultaneously, vacuum drying removes moisture, ensuring that the MXene remains dry before contacting the noble metal solution, thus creating an in-situ loading effect rather than simple mixing.

[0015] 2. The preparation method provided by the present invention adopts in-situ reduction. The method adopts calcination followed by impregnation. During the impregnation process, MXene and HAuCl4 undergo redox reaction. The reduced gold atoms undergo heterogeneous nucleation on the surface of MXene and gradually grow into uniformly dispersed gold nanoparticles. This avoids the oxidation of MXene and the shedding of noble metals caused by high temperature during heat treatment in traditional methods.

[0016] 3. The preparation method provided by the present invention has a simple preparation process, requiring only a general-purpose tube furnace and vacuum oven. The equipment is simple, no additional reducing agent is needed, no subsequent impurity removal and purification equipment is needed, and no multiple solvent changes are required for cleaning. It has advantages such as low energy consumption, low cost, and good reproducibility, which is conducive to achieving large-scale production.

[0017] 4. In the porous framework N-doped MXene-C-Au composite material provided by this invention, the three-dimensional porous carbon framework structure provides a large number of pore channels, which is beneficial to the permeation of electrolyte and the diffusion of reactant gases, thereby improving the mass transfer efficiency of electrocatalytic reaction; the N-doped carbon framework provides abundant active sites, enhancing the adsorption capacity for reaction intermediates and improving the activity of electrocatalytic reaction; MXene nanosheets are uniformly loaded in the pores of the porous carbon framework, forming a continuous two-dimensional conductive network, which enhances the electronic conductivity of the material; Au nanoparticles are uniformly distributed on the MXene surface, providing additional active sites and enhancing interfacial reaction kinetics, making it suitable for applications in electrocatalysis and supercapacitors.

[0018] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the preparation method of the porous framework N-doped MXene-C-Au composite material provided in the embodiments of the present invention; Figure 2 This is the X-ray diffraction pattern of the porous framework N-doped MXene-C-Au composite material prepared in Example 1 of this invention; Figure 3 This is the X-ray photoelectron spectrum of the porous framework N-doped MXene-C-Au composite material prepared in Example 1 of this invention; Figure 4 This is a scanning electron microscope image of the porous framework N-doped MXene-C-Au composite material prepared in Example 1 of this invention; Figure 5 This is a scanning electron microscope image of the porous framework N-doped MXene-C-Au composite material prepared in Example 2 of the present invention; Figure 6 This is a scanning electron microscope image of the porous framework N-doped MXene-C-Au composite material prepared in Example 3 of the present invention; Figure 7 This is a scanning electron microscope image of the porous framework N-doped MXene-C-Au composite material prepared in Comparative Example 1 of this invention; Figure 8 This is a scanning electron microscope image of the porous framework N-doped MXene-C-Au composite material prepared in Comparative Example 2 of this invention; Figure 9 This is a transmission electron microscope image of the porous framework N-doped MXene-C-Au composite material prepared in Example 1 of the present invention. Detailed Implementation

[0020] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the following describes in detail, with reference to the accompanying drawings and specific embodiments, a porous framework N-doped MXene-C-Au composite material and its preparation method proposed according to the present invention.

[0021] The foregoing and other technical contents, features, and effects of the present invention will be clearly presented in the following detailed description of specific embodiments in conjunction with the accompanying drawings. Through the description of the specific embodiments, a more in-depth and concrete understanding can be gained of the technical means and effects adopted by the present invention to achieve its intended purpose. However, the accompanying drawings are for reference and illustration only and are not intended to limit the technical solutions of the present invention.

[0022] It should be noted that, in this document, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified. Furthermore, the terms "comprising," "including," or any other variations are intended to cover non-exclusive inclusion, such that an article or device comprising a list of elements includes not only those elements but also other elements not explicitly listed. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the article or device comprising said element.

[0023] Existing technologies suffer from the following shortcomings: First, there is a risk of structural damage, as high-temperature heat treatment can easily lead to MXene dehydration and oxidation or interlayer structural collapse. Second, the processes are highly complex, typically requiring multiple steps such as liquid-phase deposition and high-temperature annealing. Some methods rely on expensive equipment and involve multiple solvent changes for cleaning, which is not conducive to large-scale production. Third, Au loss is severe; poorly bound noble metal ions can easily escape during vacuum drying or heat treatment, resulting in low loading rates and resource waste. Therefore, developing a simple, low-energy-consumption porous framework N-doped MXene-C-Au composite material and its preparation method that can achieve high loading rates and uniform doping is of great significance for electrode materials in high-performance electrocatalysis and supercapacitors.

[0024] To address the aforementioned issues, this invention provides a porous framework N-doped MXene-C-Au composite material. In this composite material, the N-doped carbon framework provides a three-dimensional conductive network, MXene nanosheets are loaded within the pores of the carbon framework to form a two-dimensional conductive layer, and Au nanoparticles are uniformly distributed on the MXene surface to form active sites. These three components work synergistically to enhance the electrocatalytic and conductive properties of the material.

[0025] This invention also provides a method for preparing a porous framework N-doped MXene-C-Au composite material, see [link to relevant documentation]. Figure 1 This includes the following steps S1 to S4.

[0026] S1. Obtaining polymer porous foam. Specifically, this includes: The polymer porous foam raw material is cut to obtain polymer porous foam blocks of a predetermined volume. The polymer porous foam blocks are then subjected to ultrasonic cleaning in ethanol to remove surface impurities and residues, followed by drying to obtain the polymer porous foam ready for use.

[0027] In some examples, the volume of the polymer porous foam block can be 6–10 cm³. 3 Within this range, the selected size of the polymer porous foam in this example falls within the miniaturization category, making it more suitable for precise mass transfer and microstructure control. If the size of the polymer porous foam is too large, the liquid may have difficulty penetrating to the core region, leading to the formation of unreacted zones inside. During calcination, the internal temperature rises slowly, and a large thermal gradient may occur between the outside and the inside, causing cracks or structural collapse. If the size is too small, the capacity may be limited, which is not conducive to maintaining a stable microstructure. For example, the cut polymer porous foam block can be a cube with dimensions of 2 cm × 2 cm × 2 cm. Another example is a cuboid with dimensions of 3 cm × 2 cm × 1 cm. Yet another example is a circle with a radius of 1.2 cm. It is understood that the polymer porous foam block can also be other shapes.

[0028] For example, the polymer porous foam can be one of melamine porous foam, phenolic resin porous foam, and polyurethane porous foam.

[0029] This embodiment uses polymer porous foam as the framework material. The polymer porous foam itself has a three-dimensional interconnected porous network structure. The porous carbon framework formed after carbonization can effectively support the loading of MXene nanosheets and prevent interlayer stacking. Nitrogen elements in the polymer porous foam are in-situ doped into the carbon framework during carbonization, forming an N-doped carbon framework structure, which is beneficial for improving the electrocatalytic activity of the material. Polymer porous foam is widely available, inexpensive, and conducive to large-scale production.

[0030] S2. Anneal the polymer porous foam in an inert atmosphere, heating it to 300-600℃ at a heating rate of 2-5℃ / min and holding it for 2-4 hours to obtain carbonized polymer porous foam.

[0031] This step involves annealing the porous polymer foam. During the heating process, the porous polymer foam undergoes a pyrolysis reaction, forming a porous carbon framework structure. This provides a lightweight framework with a large specific surface area for the MXene and gold nanoparticles in subsequent steps, allowing them to be more firmly supported and uniformly dispersed on the porous carbon framework. Simultaneously, nitrogen is retained to achieve N doping. Specifically, the porous polymer foam is placed in a tube furnace, and an inert protective gas (such as argon or nitrogen) is introduced as the atmosphere. The temperature is raised from room temperature to 300–600°C at a heating rate of 2–5°C / min, held at the target temperature for 2–4 hours, and then naturally cooled to room temperature to obtain the carbonized porous polymer foam. Preferably, the annealing parameters include a heating rate of 3°C / min, heating to 500°C, and holding for 3 hours.

[0032] S3. The carbonized polymer porous foam is immersed in an MXene dispersion to ensure that MXene nanosheets are uniformly adsorbed on the surface and internal pore walls of the polymer porous foam. After removal, it is dried for the first time to obtain carbonized polymer porous foam containing MXene; the concentration of MXene in the MXene dispersion is 5-20 mg / mL. The polymer porous foam is first calcined and then immersed in the MXene dispersion and gold source precursor solution to avoid the problems of MXene dehydration and oxidation, interlayer structure collapse, and easy escape of poorly bound noble metal ions caused by high-temperature heat treatment.

[0033] The impregnation time is 0.5–2 h, allowing MXene nanosheets to fully penetrate into the pore structure of the carbonized polymer porous foam. After impregnation, a first drying treatment is performed using a vacuum oven at 50–100 °C for 1–3 h to obtain MXene-containing carbonized polymer porous foam. This example uses an impregnation-drying process to load MXene. By controlling the concentration of the MXene dispersion and the impregnation time, the loading amount of MXene in the porous carbon framework can be adjusted. During impregnation, MXene nanosheets enter the pores of the porous carbon framework through physical adsorption and capillary action. Drying under vacuum conditions is beneficial for the bonding between the MXene nanosheets and the carbon framework.

[0034] In this embodiment, the impregnation time of MXene is a key parameter that determines the microstructure and macroscopic properties of the material. Different impregnation times will directly affect the dispersion, loading density and bonding strength of MXene nanosheets with the matrix. Within the range of 0.5 to 2 h, the effective loading of MXene nanosheets can be achieved without causing uneven distribution due to excessive loading.

[0035] The process of impregnating carbonized polymer porous foam in an MXene dispersion is essentially a diffusion-adsorption equilibrium process: if the MXene concentration is too low (<5 mg / mL), it is in an unsaturated stage, and the liquid cannot fully penetrate the core region of the polymer porous foam, only wetting the surface, resulting in internal voids and forming a shell-core structure. The polymer porous foam and MXene lack sufficient interfacial adhesion, making them prone to detachment. If the MXene concentration is too high (>20 mg / mL), due to the large number of -OH / (-F) groups on the MXene surface, excessive concentration may cause them to stack or self-assemble into large lumps in the solvent, losing their original two-dimensional unfolded structure. Therefore, this MXene range (5–20 mg / mL) ensures that MXene nanosheets uniformly penetrate the pores of the polymer porous foam, achieving efficient loading and enrichment of noble metals, avoiding the problems of stacking or insufficient loading common in traditional processes, thereby maximizing the active site density and structural integrity of the final composite material.

[0036] S4. Immerse the MXene-containing carbonized polymer porous foam in a gold source precursor solution and let it stand for 0.5–1.5 min. The gold source precursor solution is an aqueous solution of HAuCl4 with a concentration of 3–7 mmol / L. After standing, perform a second drying treatment using a vacuum oven at 50–100°C for 10–15 h to obtain a porous framework N-doped MXene-C-Au composite material. This embodiment uses an immersion-standing process to load Au, with a low concentration of the gold source precursor solution and a short standing time. Au ions are mainly deposited on the surface and in the pores of the MXene nanosheets. Thus, long-term drying under vacuum conditions allows Au ions to be fully reduced and firmly bound to the MXene surface. Compared with the traditional liquid phase deposition-high temperature annealing process, this invention does not require high-temperature treatment, avoiding the risks of MXene dehydration oxidation and interlayer structure collapse.

[0037] In this invention, the porous polymer foam scaffold retains its porous structure after carbonization. The carbonized porous polymer foam serves as a porous carrier, with MXene nanosheets uniformly adsorbed on its surface and internal pore walls. Gold nanoparticles formed after MXene reduction permeate the interior of the carbonized foam pore walls. The synergistic effect of these three elements effectively enhances the structural stability and metal loading rate of the N-doped MXene-C-Au composite material with a porous framework. Thus, the preparation method provided by this invention requires only one calcination step, two impregnation steps, and two vacuum drying steps; no solvent replacement or external reducing agent is needed throughout the process. The porous carbon framework supports and maintains the MXene dispersion, ensuring uniform loading of the precious metal and effectively preventing loss. Furthermore, the process is simple, requires conventional equipment, and is conducive to large-scale production.

[0038] In one embodiment of the present invention, MXene is a single-layer or few-layer MXene nanosheet; the MXene nanosheet is obtained by etching and exfoliation of the parent phase MAX material, and the chemical formula of the MXene nanosheet is M. n+1 X n T x Where n is a positive integer from 1 to 3, M is selected from any one of Sc, Ti, Zr, V, Nb, Cr and Mo, A is selected from any one of Al, Si and Ga, X is C and / or N, and T x It is a surface functional group.

[0039] In one example, the fabrication process of monolayer or few-layer MXene nanosheets includes: S31. At 30–40°C, the parent phase MAX material is subjected to liquid-phase etching reaction using an etching solution for 20–60 h to obtain two-dimensional nanosheets; wherein the etching solution is a mixture of hydrogen fluoride and hydrochloric acid, or a mixture of lithium fluoride and hydrochloric acid.

[0040] S32. Wash the two-dimensional nanosheets with deionized water until the pH of the washing solution is ≥6, and then take the supernatant to obtain a monolayer or few-layer MXene dispersion by sonication in an ice bath and centrifugation.

[0041] The following specific embodiments further illustrate the porous framework N-doped MXene-C-Au composite material and its preparation method provided by the present invention.

[0042] Example 1 This embodiment describes the preparation of a porous framework N-doped MXene-C-Au composite material and its preparation method, specifically including the following steps: S10, monolayer MXene (Ti3C2T) x Preparation of ).

[0043] (1) Preparation of Ti3AlC2MAX phase: Titanium metal powder (particle size ≤48 μm, purity 99.99%), aluminum metal powder (particle size 1~3 μm, purity 99.5%), and titanium carbide powder (particle size 2~4 μm, purity 99%) were mixed in a molar ratio of 1:1.2:2. Anhydrous ethanol was used as a grinding aid, and the mixture was ball-milled at 350 r / min for 4 h, followed by drying at 30℃ for 10 h. The mixed powder was then ground and sintered in an argon atmosphere at 1350℃ for 2 h. After cooling, it was ground through a 400-mesh sieve to obtain the MAX phase powder.

[0044] (2) Etching and stripping: 2 g LiF was slowly added to 20 mL of 9 mol / L HCl aqueous solution and stirred (500-700 r / min) to dissolve. Then, 2 g Ti3AlC2MAX phase powder was slowly added to avoid excessive exothermic reactions caused by rapid addition of the Ti3AlC2MAX phase powder. The reaction was carried out at 35℃ and 200 r / min for 24 h with stirring. The reaction product was repeatedly shaken and centrifuged with deionized water (shaking for 2 min and centrifuging at 3500 r / min for 2 min during each wash) until the pH of the supernatant was >6 (nearly neutral). The washed precipitate was dispersed in 300 mL of deionized water and deoxygenated under vacuum for 1 h. Then, it was sonicated in an ice bath for 1 h (power 220 W). Finally, it was centrifuged at 3500 r / min for 1 h, and the supernatant was collected, which is the monolayer Ti3C2T. x Suspension.

[0045] S20. Prepare porous framework N-doped MXene-C-Au composite material.

[0046] (1) Cut the melamine foam raw material into small pieces of about 2 cm·2 cm·2 cm, place them in 200 mL of ethanol and ultrasonically clean them for 30 min to remove surface impurities, and dry them in an 80°C oven to remove residual solvents to obtain melamine porous foam.

[0047] (2) Place the melamine porous foam in a tube furnace, introduce inert gas (nitrogen), heat at 500°C at a rate of 3°C / min, keep warm for 3 h, maintain the inert gas flow, and take out the sample after it cools naturally to room temperature to obtain carbonized melamine porous foam.

[0048] (3) The carbonized melamine porous foam is uniformly immersed in 30 mL of the monolayer MXene suspension prepared in step S10 with a concentration of 10 mg / mL for 1 h to ensure that the MXene nanosheets are uniformly adsorbed on the surface and internal pore walls of the pretreated melamine foam; after removal, it is placed in an 80°C vacuum oven to dry for 12 h to remove the solvent and obtain carbonized melamine porous foam containing MXene.

[0049] (4) Prepare 30 mL of HAuCl4 solution with a concentration of 5 mmol / L, completely immerse the MXene-containing melamine porous foam in the HAuCl4 solution, let it stand for 1 min to ensure that gold ions penetrate into the foam pore wall, take out the melamine porous foam, place it in an 80°C vacuum oven to dry for 12 h, and obtain a black porous framework N-doped MXene-C-Au composite material.

[0050] The porous framework N-doped MXene-C-Au composite material prepared in Example 1 is defined as composite material 1.

[0051] Example 2 The difference between Example 2 and Example 1 is that in step S20, the concentration of the monolayer MXene suspension is 5 mg / mL.

[0052] The remaining operations are the same as in Example 1. The porous framework N-doped MXene-C-Au composite material prepared in Example 2 is defined as composite material 2.

[0053] Example 3 The difference between Example 3 and Example 1 is that in step S20, the concentration of the monolayer MXene suspension is 20 mg / mL.

[0054] The remaining operations are the same as in Example 1. The porous framework N-doped MXene-C-Au composite material prepared in Example 3 is defined as composite material 3.

[0055] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S20, the concentration of the monolayer MXene suspension is 3 mg / mL.

[0056] The remaining operations are the same as in Example 1. The porous framework N-doped MXene-C-Au composite material prepared in Comparative Example 1 is defined as composite material 4.

[0057] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step S20, the concentration of the monolayer MXene suspension is 30 mg / mL.

[0058] The remaining operations are the same as in Example 1. The porous framework N-doped MXene-C-Au composite material prepared in Comparative Example 2 is defined as composite material 5.

[0059] like Figure 2 As shown, the X-ray diffraction (XRD) pattern of composite material 1 prepared in Example 1 is shown. As can be seen from the figure, the material prepared in Example 1 clearly shows the characteristic diffraction peaks of MXene, Au and C, indicating that the porous framework N-doped MXene-C-Au composite material was successfully prepared.

[0060] See Figure 3 The diagram illustrates the X-ray photoelectron spectroscopy (XPS) spectrum of composite material 1 prepared in Example 1. From... Figure 3As can be seen from the data, the porous framework N-doped MXene-C-Au composite material prepared in Example 1 contains elements such as Ti, C, Au, N, and O. Furthermore, the XPS analysis of each element shows that the porous framework N-doped MXene-C-Au composite material was successfully synthesized. Figure 9 Transmission electron microscope (TEM) image of composite material 1 prepared in Example 1 shown. Figure 2 The XRD pattern analysis results of the composite material 1 prepared in Example 1 are consistent.

[0061] See Figures 4 to 8 , Figure 4 The image shown is a scanning electron microscope (SEM) image of composite material 1 prepared in Example 1. Figure 5 The image shown is a SEM image of composite material 2 prepared in Example 2. Figure 6 The image shown is a SEM image of composite material 3 prepared in Example 3. Figure 7 The image shown is a SEM image of composite material 4 prepared in Comparative Example 1. Figure 8 The image shows the SEM image of composite material 5 prepared in Comparative Example 2. As can be seen from the image, when the MXene concentration is low (3 mg / mL), MXene does not form obvious independent lamellar structures between the carbon skeletons. When the concentration is increased to 5 mg / mL, a small amount of MXene sheets begin to appear between the C skeletons. When the MXene concentration reaches 10 mg / mL, a good interpenetrating network structure is formed between the C skeleton and the MXene sheets, with the MXene sheets uniformly anchored between the C tube walls. This retains a rich porous structure to facilitate material transport and significantly increases the loading of active materials, achieving an ideal composite of conductive skeleton and functional filler. As the concentration further increases to 20 mg / mL, multilayer stacking of MXene sheets begins to occur in local areas, with some sheets spanning across the pores, leading to a reduction in local pore size. When the concentration reaches 30 mg / mL, excessive MXene undergoes severe self-stacking and aggregation. Figure 8 On the left, it can be seen that a relatively thick blocky aggregate was formed, and during the MXene immersion experiment, MXene was deposited at the bottom of the beaker.

[0062] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a porous framework N-doped MXene-C-Au composite material, characterized in that, Includes the following steps: S1. Obtain polymer porous foam; S2. The polymer porous foam is annealed in an inert atmosphere at a heating rate of 2-5℃ / min to 300-600℃ and held for 2-4 hours to obtain carbonized polymer porous foam. S3. The carbonized polymer porous foam is immersed in MXene dispersion for treatment, and after the first drying, carbonized polymer porous foam containing MXene is obtained; the concentration of MXene in the MXene dispersion is 5-20 mg / mL; S4. Immerse the MXene-containing carbonized polymer porous foam in the gold source precursor solution and let it stand for 0.5 to 1.5 minutes. After a second drying, obtain a porous framework N-doped MXene-C-Au composite material.

2. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 1, characterized in that, In step S1, obtaining polymer porous foam includes pretreatment of the polymer porous foam raw material; The pretreatment includes: cutting the polymer porous foam raw material to obtain a volume of 6-10 cm³. 3 Polymer porous foam blocks; The polymer porous foam block was ultrasonically cleaned in ethanol and then dried to obtain the polymer porous foam.

3. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 2, characterized in that, The polymer porous foam is one of melamine porous foam, phenolic resin porous foam, and polyurethane porous foam.

4. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 1, characterized in that, In step S3, the MXene is a single-layer or few-layer MXene nanosheet; The MXene nanosheets were obtained by etching and exfoliation of the parent MAX material, and the chemical formula of the MXene nanosheets is M. n+ 1X n T x Where n is a positive integer from 1 to 3, M is selected from any one of Sc, Ti, Zr, V, Nb, Cr and Mo, A is selected from any one of Al, Si and Ga, X is C and / or N, and T x It is a surface functional group.

5. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 4, characterized in that, The preparation process of the monolayer or few-layer MXene nanosheets includes: S31. At 30-40°C, the parent phase MAX material is subjected to liquid-phase etching reaction using an etching solution for 20-60 h to obtain two-dimensional nanosheets; wherein, the etching solution is a mixture of hydrogen fluoride and hydrochloric acid, or the etching solution is a mixture of lithium fluoride and hydrochloric acid. S32. The two-dimensional nanosheets are washed with deionized water until the pH of the washing solution is ≥6. After washing, the supernatant is collected by ice bath sonication and centrifugation to obtain a monolayer or few-layer MXene dispersion.

6. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 5, characterized in that, In step S3, the immersion treatment time is 0.5 to 2 hours; The first drying process is carried out in a vacuum oven at a temperature of 50–100°C for 1–3 hours.

7. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 1, characterized in that, In step S4, the gold source precursor solution is an aqueous solution of HAuCl4, and the concentration of the aqueous solution of HAuCl4 is 3-7 mmol / L.

8. The method for preparing the porous framework N-doped MXene-C-Au composite material according to claim 7, characterized in that, The second drying is carried out in a vacuum oven at a temperature of 50–100°C for 10–15 hours.

9. A porous framework N-doped MXene-C-Au composite material, characterized in that, It is obtained by the preparation method described in any one of claims 1-8.